If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(z+4)-4(z-4)=2(z-3)+2(z-3)
We move all terms to the left:
9(z+4)-4(z-4)-(2(z-3)+2(z-3))=0
We multiply parentheses
9z-4z-(2(z-3)+2(z-3))+36+16=0
We calculate terms in parentheses: -(2(z-3)+2(z-3)), so:We add all the numbers together, and all the variables
2(z-3)+2(z-3)
We multiply parentheses
2z+2z-6-6
We add all the numbers together, and all the variables
4z-12
Back to the equation:
-(4z-12)
5z-(4z-12)+52=0
We get rid of parentheses
5z-4z+12+52=0
We add all the numbers together, and all the variables
z+64=0
We move all terms containing z to the left, all other terms to the right
z=-64
| 11-f=2 | | 2n-6n=32 | | -11=-4z+17 | | 10(3x-5)=-85 | | 16-h=5 | | -8c-10=30 | | 2x+x+(x-30)=180 | | 2x=3x/2+5 | | 5x-2(2x+6)=4-5(4-x) | | x3+3x2-23x-20=0 | | 5x-1=4x+15 | | 14x-72=9x-7 | | 3x2−3x+10=0 | | 22^(3x-1)=7^x | | 5x(2)=10 | | x^2+0.0007x-0.0000105=0 | | 15x-5=18x-29 | | 8x+39+12x-19=180 | | 8x+39=12x-19 | | 6x+66=17x-44 | | 6×x=42 | | 0.4x+0.5=0.3x+0.6 | | 5x=36−4x | | 5^(3x-5)=71 | | 1/2y=-2+10 | | (x^2+15x+56)=0 | | |3x-18|=|9x+18| | | 4(5/2x-2)-1/3(9x-3)=3x+6 | | 3=3x-3=18 | | X-9x^2+1=0 | | 10x+7=13x+4 | | 3(4x-5)+4=5(2x+5)-10 |